Ceramic laminates: planning, execution and possible failures (Research, Society and Development, 2022)
Introduction: It is known that success in the dental field is related to the correct treatment planning. As in any aesthetic treatment, in restorations with ceramic laminates, failures may occur, among them we can mention ceramic laminates with over contour that can lead to iatrogenic gingivitis; bone loss; postoperative sensitivity and also to fractures or chipping of the laminate. Objective: to identify what the literature brings about execution, failures and damage that can occur due to treatment with ceramic laminates. Methodology: a bibliographic research was carried out between 2021 and 2022 in the databases, Pubmed, Scielo, in clinical research articles, in vitro and in situ studies, systematic review, and cross-sectional study on ways of execution and failures of ceramic laminates. 150 articles were found and after reading the abstracts, 20 of them were selected according to the proposed theme.Websites and magazines were used, 20 articles were used. Result and conclusion of the study: The main factors that lead to the failure of ceramic laminates are errors in case selection, planning, laboratory failures, inadequate preparations, failures in cementation, and lack of follow-up. In view of this, the theoretical and practical knowledge of the professional in cases of ceramic laminates is of paramount importance, so that such failures can be minimized.